Good game : Christianity and the culture of sports - Hoffman, Shirl J., 1939- (Waco, Tex. : Baylor University Press, 2010)
Good Game retells numerous fascinating stories from the world of ancient and contemporary sports and draws on the history of the Christian tradition to answer "What would it really mean to think Christianly about sport?" --from publisher description
Sports and the early church -- Proscribing, controlling, and justifying sport -- Bowling, bicycles, and other snares of the devil -- The church heads for the playground -- The rise of sport evangelism -- Christians and the killer instinct -- Building and sacking the temple -- Sport and the sub-Christian values -- Touchdowns and slam dunks for Jesus -- Prayers out of bounds -- Notes toward a well-played game.
Includes bibliographical references (p. 293-328) and index.
Keywords: Sports -- Religious aspects -- Christianity; Sports -- Moral and ethical aspects; Sports -- Social aspects; Sports -- Moral and ethical aspects; Sports -- Religious aspects -- Christianity; Sports -- Social aspects